2020
DOI: 10.3389/fpsyt.2020.540738
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Background Noise and Auditory Hallucinations on Phonemic Mismatch Negativity (MMN) and P3a Processing in Schizophrenia

Abstract: Auditory hallucinations (AHs) are among the cardinal symptoms of schizophrenia (SZ). During the presence of AHs aberrant activity of auditory cortices have been observed, including hyperactivation during AHs alone and hypoactivation when AHs are accompanied by a concurrent external auditory competitor. Mismatch negativity (MMN) and P3a are common ERPs of interest within the study of SZ as they are robustly reduced in the chronic phase of the illness. The present study aimed to explore whether background noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Their findings showed an abnormal roving MMN profile for the AH group, while there was no difference between the healthy comparison group and the combined schizophrenia group (with and without AHs). In a similar vein, Francis et al, (2020) found reduced MMNs for hallucinating patients compared to non-hallucinating patients when studying the influence of background noise in auditory processing. They concluded the presence of AHs may specifically impair the MMN.…”
Section: Introductionmentioning
confidence: 71%
“…Their findings showed an abnormal roving MMN profile for the AH group, while there was no difference between the healthy comparison group and the combined schizophrenia group (with and without AHs). In a similar vein, Francis et al, (2020) found reduced MMNs for hallucinating patients compared to non-hallucinating patients when studying the influence of background noise in auditory processing. They concluded the presence of AHs may specifically impair the MMN.…”
Section: Introductionmentioning
confidence: 71%
“…It has also been shown to predict conversion into psychosis in children at high-risk ( Bodatsch et al, 2011 ; Perez et al, 2014 ). And most recently, treatment-related improvement in MMN measures was shown to be associated with improvements in clinical features (hallucinations; Francis et al., 2020 ) and attention and memory processing ( Javitt et al, 2018 ). Thus, further reinforcing the implication of MMN as a translatable neural biomarker aiding in the development of novel therapeutic methods and pharmaceuticals in SCZ ( Butler et al, 2012 ; Green et al, 2009 ; Nagai et al., 2013 ; Tada et al, 2019 ; Todd et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%